2022
DOI: 10.1155/2022/6331956
|View full text |Cite
|
Sign up to set email alerts
|

An EEG Classification-Based Method for Single-Trial N170 Latency Detection and Estimation

Abstract: Event-related potentials (ERPs) can reflect the high-level thinking activities of the brain. In ERP analysis, the superposition and averaging method is often used to estimate ERPs. However, the single-trial ERP estimation can provide researchers with more information on cognitive activities. In recent years, more and more researchers try to find an effective method to extract single-trial ERPs, because most of the existing methods have poor generalization ability or suffer from strong assumptions about the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The frequency variants with respect to different time spans can be characterized by the continuous wavelet transform, short-time Fourier transform, and wavelet packet transform [ 13 ]. The research work of Zang et al [ 8 ] has demonstrated the merits of joint time-frequency features in the epileptic seizure detection application.…”
Section: Perspectivesmentioning
confidence: 99%
See 4 more Smart Citations
“…The frequency variants with respect to different time spans can be characterized by the continuous wavelet transform, short-time Fourier transform, and wavelet packet transform [ 13 ]. The research work of Zang et al [ 8 ] has demonstrated the merits of joint time-frequency features in the epileptic seizure detection application.…”
Section: Perspectivesmentioning
confidence: 99%
“…Detection of amplitude and latency components in a single-trial EEG signal requires a series of artifact removal, feature extraction, and event-related potential (ERP) identification procedures. In [ 8 ], Zang et al developed an effective machine learning technique for latency detection in single-trial EEG signals, instead of the conventional superposition and average method. Two different EEG data sets (i.e., simulated N170 and real P50 recordings) were tested for the performance evaluation purpose.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations